Peningkatan Kualitas Kokon dari Beberapa Persilangan Hibrida Ulat Sutra (Bombyx mori L.) (Improved Cocoon Quality of Multiple Silkworms (Bombyx mori L.) Hybrid Crosses) - Retno Agustarini; Lincah Andadari; Yetti Heryati; Herman Sari; Eyet Mulyati (Jurnal Penelitian Hutan Tanaman, 2022)
ABSTRACTBombyx mori is a silk-producing insect with high economic value. As an agricultural country, Indonesia has great potential for developing the natural silk industry, but the problem of silkworm seeds constrains its implementation. The purebred crossing to develop hybrids is one of the efforts to overcome the problem of seed quality. The study aimed to obtain the performance of alternative races and candidates for silkworm seeds other than those already commercialized. The stages of rearing silkworms were carried out using a Randomized Block Design, with six treatments and three replications. The treatments conducted were: Japanese crosses (927 x 919 and 919 x 927), Chinese crosses (930 x 403, 403 x 930, 804 x P208, and P208 x 804). Crosses of Chinese races have advantages, especially in the short life cycle, morphological stability, number of eggs, and percentage of hatching to cocoon quality. The cross of 403 x 903 can be a superior hybrid alternative to develop because, overall, it shows high results on egg and cocoon quality. Keywords: Bombyx mori, cross, Chinese races, Japanese races, cocoonABSTRAKBombyx mori merupakan serangga penghasil sutra bernilai ekonomi tinggi. Indonesia sebagai negara agraris sangat potensial untuk pengembangan persutraan alam, namun dalam pelaksanaannya terkendala permasalahan bibit ulat sutra. Salah satu usaha mengatasi permasalahan kualitas bibit adalah pengembangan hybrid melalui persilangan ras murni. Tujuan penelitian adalah untuk mendapatkan performa ras dan kandidat bibit ulat sutra alternatif selain yang sudah dikomersialkan. Tahapan pemeliharaan ulat sutra dilakukan menggunakan rancangan penelitian Rancangan Acak Kelompok, dengan 6 perlakuan dan 3 ulangan. Perlakuan yang dilakukan: Persilangan ras Jepang (927 x 919 dan 919 x 927), persilangan ras China (930 x 403, 403 x 930, 804 x P208, P208 x 804). Persilangan galur dari ras China mempunyai keunggulan terutama pada pendeknya siklus hidup, stabilitas morfologi, jumlah telur dan presentase penetasan sampai dengan kualitas kokonnya. Persilangan 403 x 903 dapat menjadi alternatif hibrid unggulan untuk dikembangkan karena secara keseluruhan menunjukkan hasil tinggi pada kualitas telur dan kokon.Kata kunci:  Bombyx mori, persilangan, ras China, ras Jepang, kokon